Design and Evaluation of Miconazole Nitrate loaded Nanostructured Lipid Carriers (NLC) for improving the Antifungal therapy - Gajanan S Sanap, Guru Prasad Mohanta (Journal of Applied Pharmaceutical Science, 2013)
The aim of this study was to prepare and evaluate gels incorporating nanostructured lipid carriers (NLC) of Miconazole nitrate (MN) for systemic delivery of the active after topical application. MN has been used as model drugs to be incorporated into nanostructured lipid carriers, once they are very well established as anti-mycotics for the treatment of topical fungal infections. NLC designed for topical administration of MN, were prepared by the hot high pressure homogenization technique. This MN-NLC was characterized for particle size, entrapment efficiency, and SEM. The lipid nanoparticles were incorporated in gels for convenient topical application and were evaluated forfor particle size, Rheological analysis Texture analysis , In vitro drug release studies and Ex Vitro skin permeation Studies. The preparation of aqueous NLC dispersions with a mean particle size lower than 300 nm has been obtained with uniform size distribution (PI < 0.350). The prepared semi-solid systems showed mean particle size remained lower than 250 nm and PI remained lower than 0.500 after 3 months of storage. An initial rapid release was observed in the case of Marketed gel, whereas MN- NLC Gel depicted a slow initial release with a lag time of 0.5 h and 1 h, respectively. High amount of MN release was facilitated through abdominal skin of rats from marketed gel than MN-NLC Gel. Research work could be concluded as successful development of MN-loaded NLC-bearing hydrogel to increase the encapsulation efficiency of colloidal lipid carriers with advantage of improved performance in terms of stability and provides a sustaining MN topical effect as well as faster relief from fungal infection.
Keywords: Miconazole nitrate,Nano structured lipid carriers (NLC), Topical gels, Topical delivery.